In Vitro Effect of Sodium Bicarbonate on Tooth Discoloration: Effect of Sodium Bicarbonate on Tooth Discoloration - Valian, Azam; Moazeni, Marjan; Kheirkhah Dabbagh, Neda (Journal of Dental School, 2023)
Objectives The present experimental study aimed to assess the in vitro effect of sodium bicarbonate (SB) on tooth discolouration. Methods Forty-five extracted anterior teeth were decoronated 2 mm apical to the cementoenamel junction. The crowns were immersed in tea solution for 7.5 days. The teeth were divided into three groups (n = 15 per group) on a random basis. The groups were exposed to either SB paste 94%, hydrogen peroxide (HP) 40%, or carbamide peroxide (CP) 45%. Then, teeth were bleached according to the manufacturers' instructions. Next, all tooth samples were immersed again in tea solution for 10 min. The CIE L*a*b* colour parameters of the teeth were evaluated at baseline (T1), after primary staining (T2), after bleaching (T3), and after re-staining (T4) using a spectrophotometer. The enamel surface morphology of one sample from each group was evaluated pre- and post-bleaching using scanning electron microscopy (SEM). Within-group and between-group comparisons were made using repeated measures ANOVA and Tukey’s test. Results 94% of cases had color change(∆E) more than 3.5 with no enamel surface wear after Applying SB. HP showed a maximum bleaching effect of ∆E = 8.77. After re-staining, the SB group showed minimal staining (∆E = 3.77) compared to the HP and CP groups. Conclusion The present findings show that SB can chemically resolve tooth discolouration and prevent re-staining. Considering its low abrasiveness, optimal safety, low cost, antimicrobial activity, and availability, it seems to be ideal for use at home.